The adventures of spider: West african folktales - Cooper, Arkhurst Joyce (New York : Scholastic, 1964)
Presents six tales about spider, including those which explain how he got a thin waist and a bald head and why he lives in ceilings and dark corners.
Keywords: Anansi (Legendary character) -- Legends; Folklore- -- Africa west; Spiders -- Folklore